Functional Interaction Map of Lyssavirus Phosphoprotein: Identification of the Minimal Transcription Domains - Jacob, Yves (American Society for Microbiology, 2001)
Lyssaviruses, the causative agents of rabies encephalitis, are distributed in seven genotypes. The phylogenetically distant rabies virus (PV strain, genotype 1) and Mokola virus (genotype 3) were used to develop a strategy to identify functional homologous interactive domains from two proteins (P and N) which participate in the viral ribonucleoprotein (RNP) transcription-replication complex. This strategy combined two-hybrid and green fluorescent protein–reverse two-hybrid assays in Saccharomyces cerevisiae to analyze protein-protein interactions and a reverse genetic assay in mammalian cells to study the transcriptional activity of the reconstituted RNP complex. Lyssavirus P proteins contain two N-binding domains (N-BDs), a strong one encompassing amino acid (aa) 176 to the C terminus and a weak one in the 189 N-terminal aa. The N-terminal portion of P (aa 52 to 189) also contains a homomultimerization site. Here we demonstrate that N-P interactions, although weaker, are maintained between proteins of the different genotypes. A minimal transcriptional module of the P protein was obtained by fusing the first 60 N-terminal aa containing the L protein binding site to the C-terminal strong N-BD. Random mutation of the strong N-BD on P protein identified three highly conserved K residues crucial for N-P interaction. Their mutagenesis in full-length P induced a transcriptionally defective RNP. The analysis of homologous interactive domains presented here and previously reported dissections of the P protein allowed us to propose a model of the functional interaction network of the lyssavirus P protein. This model underscores the central role of P at the interface between L protein and N-RNA template.